Forced feeding for anorexic patient? - Di Pietro, Maria Luisa; Conte, Gianluigi; Lucattini, Adelia; Spagnolo, Antonio G. (Medicina e Morale, 1993)
The Authors study the case of M.A., an 18 year old anorexic giri who, once hospitalized, refused to be treated. During an episode when she lost consciousness, the physicians decided to begin to not only treat her, but also to supply her with enteral feedings by a naso-gasric tube. This case raises numerous ethical and legai questions that are relevant to medical practice: when faced with risking on a life, does the patient have the right not to accept treatment? What respect should a patient with this disease be given? Can the physicians make the decision to force feed the patient even when there is an explicit refusal? The answers come from the ethical and legal evaluation of the conflict between the patient's right to decide about his/her own life and health, and the phisician's right and duty to safeguard the physical life of the patient.